Development of Corporate Social Responsibility Implementation (Study in Indonesia and Malaysia) - Ariani, Riska Septi; Hwihanus, Hwihanus; Ramadanthy, Fernianda Wahyu (Indonesian Journal Publisher, 2024)
This comparative analysis explores the development and impact of Corporate Social Responsibility (CSR) in Indonesia and Malaysia, highlighting differences in their frameworks, developmental trajectories, and outcomes. Indonesia’s regulatory-driven approach, established through laws like Law No. 40/2007, mandates CSR activities for companies, particularly those in natural resources. While this has led to significant contributions from large corporations in community development and environmental sustainability, challenges in enforcement, resource limitations among SMEs, and a gap between policy and genuine practice hinder the overall effectiveness. Conversely, Malaysia’s blend of regulatory requirements and voluntary initiatives promotes corporate accountability and transparency. Policies such as the Silver Book and mandatory sustainability reporting by Bursa Malaysia have driven strategic integration of CSR into business operations. Malaysian companies, exemplified by Petronas, Maybank, and Nestlé Malaysia, align their CSR initiatives with the United Nations Sustainable Development Goals (SDGs), resulting in more consistent and impactful outcomes. The analysis underscores that while Indonesia ensures widespread participation through regulatory mandates, it faces challenges in enforcement and strategic depth. Malaysia’s approach fosters innovation and accountability, leading to more effective CSR practices. By learning from each other’s experiences, both countries can enhance their CSR efforts, contributing to sustainable development and fostering social and environmental well-being in Southeast Asia.